1995
DOI: 10.1021/ja00109a010
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle Formation from N-Alkylindoles: Implications for Tryptophan-Water Interactions

Abstract: Previously unreported indoles having hexyl (2), decyl (3), octadecyl (4), and cholestanylacetoxy (5) groups attached to nitrogen have been prepared. A-Methylindole (1) and 2 did not form aggregates detectable by laser light scattering but compounds 3-5 did so. Formation of vesicles was confirmed by size-exclusion chromatography, dye entrapment, and freeze-fracture electron microscopy. The surprising ability of indole to serve as a head group in single-chain, amphiphilic molecules is discussed relative to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 0 publications
1
33
0
Order By: Relevance
“…Compounds 3b-e further show good solubility in MeCN, THF, DMSO, and DMF. The decyl chains give 3d a greasy texture, in line with the amphiphilic properties of 1-decylindole reported by Abel et al [15]. Variation of the N-substituent in this new [4Fe-4S] cluster family thus allows effective tuning of cluster lipophilicity.…”
Section: -Methylindole-3-thiol (2b)supporting
confidence: 81%
See 1 more Smart Citation
“…Compounds 3b-e further show good solubility in MeCN, THF, DMSO, and DMF. The decyl chains give 3d a greasy texture, in line with the amphiphilic properties of 1-decylindole reported by Abel et al [15]. Variation of the N-substituent in this new [4Fe-4S] cluster family thus allows effective tuning of cluster lipophilicity.…”
Section: -Methylindole-3-thiol (2b)supporting
confidence: 81%
“…Unsubstituted indole-3-thiol 2a [7,9] and its methyl- [13] and benzyl-substituted [6] analogs 2b and 2e have been prepared previously by Harris's method, although synthetic details for 2b and 2e were not reported. Two alkyl-substituted indole-3-thiols with longer aliphatic substituents (2c = pentyl, 2d = decyl) were prepared analogously from the known compounds 1-pentylindole [14] and 1-decylindole [15]. The two-step yields of thiols 2b-e ranged from 40% to 63%.…”
Section: -Methylindole-3-thiol (2b)mentioning
confidence: 99%
“…An examination of the KcsA voltage gated potassium channel from Streptomyces lividans suggests that the indole residues of all the tryptophans in the structure occur at the insulator-midpolar boundary [45]. Tryptophan is the rarest of the 20 common amino acids and appears to play an important role as a stabilizing element [46][47][48] (Fig. 6).…”
Section: Design Criteria For Hydraphilesmentioning
confidence: 99%
“…21 We found that treatment with NaH in THF followed by reaction with an alkyl halide afforded the N-alkylated indoles in yields of about 60%. 22 The by-product was likely the 3-isomer, but this was not isolated. A similarly conducted reaction using LiH instead of NaH gave the corresponding 3-alkyl derivatives.…”
Section: Indole As An Amphiphilic Head Groupmentioning
confidence: 99%